Propuesta de intervención psicopedagógica a través del uso de la plataforma TOMi digital para mejorar la comprensión lectora en estudiantes de la carrera de Educación Especial de la Universidad Nacional de Loja, periodo 2024 - 2025 - Zurita Díaz, Tatiana Anahí (2025)
Reading comprehension is essential in the training process in any field because it allows to interpret, analyze and reflect on the meaning of the texts, without this, people face difficulties to understand key ideas, therefore it can be a limitation for university students who have not been able to develop this skill in their learning process, that is why the objective of this research is to analyze the psychopedagogical intervention through the use of the digital TOMi platform as an instrument to improve reading comprehension in students of the Special Education Career of the National University of Loja, period 2024-2025. The research methodology was a mixed approach, non-experimental, descriptive and cross-sectional design. The sample was intentional and consisted of 36 first-term students and 3 teachers of the career. Semi-structured interviews and the ICLAU instrument were applied to evaluate the levels of reading comprehension in five dimensions: literal, reorganization, inferential, critical and appreciation. The results revealed that, although students showed strengths in literal and inferential comprehension and a predominant average level in appreciative comprehension, they presented significant difficulties in reorganization and critical analysis, which indicated the need to develop a deeper connection with the texts. The findings demonstrated that, although students possess certain reading skills, it is necessary to work in specific areas to develop a more comprehensive reading comprehension that covers both basic and advanced skills, as well as reflecting the need to incorporate technological tools such as TOMi digital, which will allow the strategies used by teachers to be strengthened in order to promote significant learning in relation to reading comprehension